GERAKAN MASYARAKAT DALAM MEMBENTUK KENEGERIAN TIGA LORONG BATURIJAL HULU SEBAGAI DESA ADAT DI KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU TAHUN 2014-2015 - Adli Hirzan; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research entitled "Community Movement in Establishing Kenegerian Three Upper Baturijal Lorong As Indigenous Villages In Peranap District Indragiri Hulu Regency Year 2014-2015". This form of research is based on the existence of Law Number 6 Year 2014 About the Village. Based on the provisions of the rules for determining customary villages, then the three areas of Lorong Baturijal Hulu areas to be custom villages in Peranap District. How is the community movement in realizing the customary village in Kenegerian Tiga Lorong and its failure factor. The purpose of this study is to describe the movement and efforts of the community and internal and external barriers in forming the Kenegerian Three Lorong Baturijal Hulu as a custom village in Peranap District Indragiri Hulu Regency 2014-2015. The benefit of this research is as a material of scientific information for researchers who want to study the movement of society in forming custom village. The research method used is qualitative descriptive by using basic descriptive qualitative research analysis with interactive analysis model. There are two theories used, namely the theory of social movements and the concept of custom village formation. The results showed that in the social movement stage decline ending failure, and there are factors of failure of community movement in determining Kenegerian Three Lorong Baturijal Hulu as custom village in Kecamatan Peranap.Keyword: Movement of Society, Desa Adat